(untitled) (Global Journal of Computer Science and Technology, 2016)
In the paper created a new encryption algorithms GOST281472013;892013;IDEA82013;4 and GOST281472013;892013;RFWKIDEA82013; 4 based on networks IDEA82013;4 and RFWKIDEA82013;4, with the use the round function of the encryption algorithm GOST 281472013;89. The block length of created block encryption algorithm is 256 bits, the number of rounds is 8, 12 and 16.